2020
DOI: 10.21163/gt_2020.151.02
|View full text |Cite
|
Sign up to set email alerts
|

Gis-Based Flood Hazard Mapping Using Hec-Ras Model: A Case Study of Lower Mekong River, Cambodia

Abstract: Rivers are the main water sources for human and animals' lives. Unfortunately, they have been frequently damaged by flooding. Flooding has affected and threatened not only human's lives and infrastructures but also the environmental capital. This study aims to determine the application of flood frequency analysis integrated with the GIS and HEC-RAS models to prepare a multi-return period flood hazard map in the Lower Mekong River of Cambodia. A 30-year peak discharge (Kampong Cham gauging station) with a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…HEC-RAS is one of the popular opened source software with a Graphical User Interface (GUI) that can do hydraulic simulations and develop the flood maps for a river system of steady flow, unsteady flow, and sediment transport (Ly et al, 2018). Kim et al (2020) used HEC-RAS combined with RS for flood hazard mapping in the Lower Mekong River. The study showed that 2011 and 2013 historical floods influenced most of the flood depth considering return periods.…”
Section: Rs Application On Flood Analysis Over Cambodiamentioning
confidence: 99%
See 2 more Smart Citations
“…HEC-RAS is one of the popular opened source software with a Graphical User Interface (GUI) that can do hydraulic simulations and develop the flood maps for a river system of steady flow, unsteady flow, and sediment transport (Ly et al, 2018). Kim et al (2020) used HEC-RAS combined with RS for flood hazard mapping in the Lower Mekong River. The study showed that 2011 and 2013 historical floods influenced most of the flood depth considering return periods.…”
Section: Rs Application On Flood Analysis Over Cambodiamentioning
confidence: 99%
“…S-Band Doppler weather radar meteor 650C, which has a range of 450 km located in Phnom Penh was not used in any flood analysis over Cambodia. (Hazarika et al, 2007;Kim et al, 2020;Liu et al, 2019;Ly et al, 2018;Son et al, 2019;Try et al, 2019) Flood (Kim et al, 2019;Mohammed et al, 2018;Sakamoto et al, 2007;Siev et al, 2016;Tangdamrongsub et al, 2016;Vichet et al, 2019;Yu et al, 2019) Flood damage assessment DEM * Landsat-8 * UNOSAT * RRI (Chung et al, 2019) * is number of studies have been used…”
Section: Gaps Of Flood Analysis Under Rs Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Geographic Information System (GIS) mapping applications vary to flood hazard mapping, flood hazard management, hydrological data storing and management. Especially, a combination of GIS (Geographic Information System) and HEC-RAS (Hydrologic Engineering Center-River Analysis System) has a great capability in the simulation of flood hazard maps (Kim et al, 2020). Out of all-natural hazards in the world, flood is the mostcommon one.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the advantages of HEC-RAS 2D itself are that it can simulate flooding in various flood scenarios (Ongdas et al, 2020) and estimate the level of flood depth. The results of UAV processing are used as terrain input in HEC-RAS (Mourato et al, 2017), and the discharge value is also inputted so that it can produce flood inundation modeling through simulation of the desired scenario (Kim et al, 2020). In this way, the flood modeling map produced will be much better at representing the geometry of the Kaliputih River in Kemiri Village, Panti-East Java District.…”
mentioning
confidence: 99%